Description of Student Performance in the Clinical Rotation of Forensic Medicine Period January-December 2019 in Faculty of Medicine, Syiah Kuala University - Taufik Suryadi; Kulsum Kulsum (Budapest International Research and Critics University, 2020)
Introduction: learning activities can be effective and achieved accordingly with what is expected if the student gets the goal learning in accordance with knowledge, attitudes and skills. Methods: the study is undertaken to investigate the success of students in rotation of forensic medicine. This study was carried out in the Faculty of Medicine, Syiah Kuala University, Banda Aceh, Indonesia. As many as 101 medical students were included in the study (39 male and 62 female), grouped in 16 groups. The instrument used in this study was a recapitulation document of clinical rotation student scores in 2019. Results and Discussion: the best average score of 89.47 was achieved by the group XV, the best average achievement index was 4.0 ( group XV), the best male student score 90 (group VI), the best female student score 91 (group III), the average male student score is 80.22, the average female student score is 81.12, the average grade cognitive 64,27, psychomotor 74,20, affective 80,90, average achievement index is 3,35 for male student and 3,67 for female student. Conclusion: the female student is better than male student performance both in psychomotor and affective, but in cognitive aspect is similar relatively. In general, in 2019 the achievements of students in clinical rotation of forensic medicine are good but need to be improved in the cognitive aspect.